Identification of Groundwater Potential Zones Using Remote Sensing and GIS Technique: A Case Study of the Ketungau Basin in Sintang, West Kalimantan - Ajun Purwanto; Paiman Paiman; Dony Andrasmoro; Eviliyanto Eviliyanto; Rustam Rustam (Indonesian Journal of Geography, 2023)
Groundwater is one of the most valuable natural resources in Sintang, but essential basic information regarding its properties and characteristics is presently unavailable. Currently, systemic and uniform investigations, as well as groundwater potential zones mapping are yet to be conducted within the framework of basin area units to support development activities. Therefore, this study aims to identify and map groundwater potential zones using remote sensing and GIS. The employed data were obtained from drainage density, slope steepness, straightness density, total rainfall, lithology, soil type, and land use land cover. The method applied was an interpretation of secondary data, which included a) identification and evaluation of criteria, b) data collection, c) preprocessing, and e) reclassification, while the analysis technique used was a weighted overlay. The results showed that the study location has five classes of groundwater potential zones, namely highly potential, potential, moderate, non-potential, and highly non-potential with areas of 120,754.08 ha (20.62%), 220,693.71 ha (37.69%), 109,668.44 ha ( 18.73), 93,404.38 ha (15.95%), and 41,068.31 ha (7.01%), respectively. Highly potential and groundwater potential zones were identified in the central, eastern, and western parts of the Ketungau basin. In contrast, the dominant non-potential and highly non-potential zones were found along the northern basin boundary. Based on the results, remote sensing and GIS approaches are practical tools for identifying groundwater potential zones, which can be used to determine policies related to groundwater utilization.